Green Schools: : Integrating Sustainability in School Curriculum - Goswami, Tisha; Ahmad, Ansar (Voices of Teachers and Teacher Educators, 2024)
Education plays a crucial role in disseminating the meaning of sustainable development. It addresses the integration of all dimensions of sustainability, i.e., social, environmental, cultural and economic. Therefore, it is important to include Education for Sustainable Development (ESD) at all levels of education across the world. ESD leads to the holistic development of learners, and also prepares them to understand and respond to diverse scenarios related to sustainability. Therefore, it becomes important to understand how deeply ESD is implemented in schools to transform them into green schools. For this study, a sample of 90 teachers and 18 principals teaching at the middle stage of schooling was purposively selected from 18 Delhi schools. Checklist, open-ended questionnaires and semi-structured interviews were used to collect data for the mixedmethod approach. The findings revealed that majority of the schools faced challenges in incorporating ESD into the curriculum and had insufficient facilities to qualify as green schools. Moreover, teachers need to take more initiatives to urgently integrate sustainable development into the teaching–learning process. Therefore, it is essential for schools to integrate ESD into their curriculum to create green schools, a necessity in this globalised world. The study concludes that ESD is an important effort to rethink about the education system at various levels, thereby contributing to building sustainable societies.